Combined Administration of Metformin and Atorvastatin Attenuates Diabetic Cardiomyopathy by Inhibiting Inflammation, Apoptosis, and Oxidative Stress in Type 2 Diabetic Mice - Jia, Weikun; Bai, Tao; Zeng, Jiang; Niu, Zijing; Fan, Daogui; Xu, Xin; Luo, Meiling; Wang, Peijian; Zou, Qingliang; Dai, Xiaozhen (Frontiers in Cell and Developmental Biology, 2021)
Diabetic cardiomyopathy (DCM), a common complication of diabetes mellitus, may eventually leads to irreversible heart failure. Metformin is the cornerstone of diabetes therapy, especially for type 2 diabetes. Statins are widely used to reduce the risk of cardiovascular diseases. In this study, we aimed to investigate whether combined adminstration of metformin and atorvastatin could achieve superior protective effects on DCM, in addition to elucidate its molecular mechanism. Here, db/db mouse(9-10 week-old) was were randomly divided into 4 groups, including sterile water group (DM), metformin group (MET, 200 mg/kg/day), atorvastatin group (AVS, 10 mg/kg/day), and combination therapy group (MET+AVS). Mice were treated with different drugs via gavage once per day for 3 months. After 3 months of treatment, the pathological changes (inflammation, fibrosis, hypertrophy and oxidative stress makers) were detected by histopathological techniques, as well as Western blotting. The H9C2 cardiomyocytes were treated with palmitate (PAL) to mimic diabetic condition. The cells were divided into control group, PAL treatment group, MET + PAL treatment group, AVS + PAL treatment group and MET + AVS + PAL treatment group. The effects of MET and AVS on the cell viability and inflammation of H9C2 cells subjected to PAL condition were evaluated by terminal deoxynucleotidyl transferase-mediated dUTP nick‐end labelling (TUNEL) assay, immunofluorescence staining and western blotting. Both MET and AVS prevented diabetes-induced fibrosis, hypertrophy and inflammation. The combination therapy showed superior effects in protecting myocardial tissue against diabetes-induced injury. Mechanistically, combination therapy significantly inhibited oxidative stress and the expression levels of inflammation-related proteins, e.g., NLRP3, caspase-1, interleukin-1β (IL-1β), Toll-like receptor 4 (TLR4), P-p65/p65, in both cardiac tissues and H9C2 cells. TUNEL assay showed that combination therapy significantly attenuated the apoptosis of cardiomyocytes, decreased the expression level of pro-apoptotic-related proteins, such as cleaved-caspase-3 and BAX, and enhanced the expression level of anti-apoptotic protein (Bcl-2). Furthermore, combination therapy remarkably upregulated the expression levels of 5′-AMP-activated protein kinase (AMPK) and SIRT-1. Our findings indicated that the anti-inflammation and anti-apoptosis effects of combination therapy may be related to activation of AMPK/SIRT-1 signaling pathway.